India in Florence: Angelo de Gubernatis and the shaping of Italian Orientalism (1860-1900) - Vicente, Filipa (2021)
Florence as the capital for a new united Italy became a flourishing, and brief, centre for indian studies. This experience was always entangled with Angelo De Gubernatis’s biography and initiatives and when he left for Rome, the city lost its role. Having decided to leave his rich and prolific archive in Florence’s main public library meant, however, that Gubernatis returned to the city and placed it on the map of 19th century “oriental studies”. Through congresses, exhibitions, museums, a worldwide network of correspondents, journals, academic teaching and travel writing and the protagonism of Angelo de Gubernatis, “oriental”, “India” and “Sanskrit” became recurrent words in the Renaissance city and spaces of physical and intellectual encounter between scholars of different origins. In my paper I will also analyse how the investment in “oriental studies” became part of a strategy of affirmation of the new nation of Italy within Europe and within a wider geography were knowledge circulated through written, visual and material forms.